Implementación del proceso contable en la “Farmacia Oriental” del canton Limon Indanza, provincia de Morona Santiago, periodo: septiembre del 2013. - Reinoso Borja, Lourdes Del Pilar (2014)
This research entitled "IMPLEMENTATION OF THE ACCOUNTING PROCESS IN PHARMACY" ORIENTAL "THE CANTON Indanza LIMON, Morona Santiago province, PERIOD: SEPTEMBER 2013" is aimed at structuring tool for an accounting firm farnaceuticos products. This work was done in order to give its owner a contribution of how to take proper control and management of their economic and financial resources to enable it to know the real situation of your business to decision making; and as a prerequisite to obtain the degree of Engineer in Accounting and Auditing requirement; it was necessary to make a survey of an initial inventory and the collection and physical verification of the source documents, a memorandum of operations and design of accounting records for the implementation of the accounting process By implementing business accounts were met with the proposed objectives and developing a plan and manual for specific accounts, inventory is I structure, records and ancillary accounting was designed and by the process of financial statements as optimal and efficient information to be generated the right decisions your business. Finally we conclude that once developed the accounting process is the same as ordered and classified by determining net income so the owner recommended stockholders accept proposed design and use it to continue implementation of accounting that have been and methodologically developed technique considering the type of economic activity, control and allow normal operation of the warehouse and thus may have relevant, reliable and comparable financial statements for timely decision making.